The dilemma of frontline servant leadership: The conflict between top management directives and grassroots employee wellbeing and retention. - Zhiwen Song; Ziyu Xu; Binglin Martin Tang; Wai Nga Leong (PLoS ONE)
Servant leadership in the workplace involves providing services and cultivating trust amongst subordinates. However, leadership dynamics can be distorted when hospitality frontline managers assume leadership roles by strictly adhering to top management strategic directives. This study aims to examine how constraints imposed by top management influence the management styles of frontline managers within the hospitality industry. The current study delved into the interplay amongst servant leadership, employee wellbeing and retention, highlighting the pivotal role of service climate, procedural justice and customer satisfaction as moderating variables. In this research, partial least squares structural equation modelling was used to test the research model, using data collected from 485 respondents. Findings underscore the critical role of hospitality frontline managers in aligning with organisational strategic directives, a requirement that may compromise their servant leadership style. Poor service climate and procedural justice may result from this alignment. The current study emphasises that strictly adhering to predetermined top management decisions can influence the outcomes of servant leadership-an often-overlooked factor in existing research. Lastly, this research enriches the literature on the effect of servant leadership on employee retention.